1997
DOI: 10.2337/diacare.20.8.1304
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy, Promoter (4G/5G) Polymorphism of PAI-1 Gene, and PAI-1 Activity in Pima Indians With Type 2 Diabetes

Abstract: Although diabetic retinopathy in Pima Indians with type 2 diabetes is not associated with PAI-1 activity, subjects with the 4G/4G and 4G/5G genotype had a higher prevalence of retinopathy compared with 5G/5G PAI-1genotype. These preliminary findings indicate that in Pima Indians with type 2 diabetes, presence of the 4G allele of the PAI-1 gene was associated with a higher risk of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
3
26
2
Order By: Relevance
“…The transforming growth factor-␤ gene has shown evidence of association only with proliferative retinopathy (28). A previous candidate gene study in the Pimas reported a modest association between retinopathy (as assessed by fundoscopy) and a polymorphism in the promoter region of the plasminogen activator inhibitor 1 gene on chromosome 7 (29). None of these genes, however, map to the area of linkage identified in the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…The transforming growth factor-␤ gene has shown evidence of association only with proliferative retinopathy (28). A previous candidate gene study in the Pimas reported a modest association between retinopathy (as assessed by fundoscopy) and a polymorphism in the promoter region of the plasminogen activator inhibitor 1 gene on chromosome 7 (29). None of these genes, however, map to the area of linkage identified in the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…In women, the 4 G-allele predicted a slightly increased risk of myocardial infarction (Leander et al 2003). In contrast, the 5 G/5 Ggenotype of PAI-1 has been found associated with myocardial infarction in women (Yamada et al 2002) whereas in 171 type 2 diabetic Pima Indians, subjects with the 4 G/4 G and the 4 G/5 G genotype had a higher prevalence of retinopathy (Nagi et al 1997). In 519 Caucasian diabetic patients (192 with type 1 and 327 with type 2 diabetes) (Mansfield et al 1995b) and, in another study, in 204 type 2 diabetic patients no association between PAI-1 polymorphism and the prevalence of retinopathy could be identified (GlobocnikPetrovic et al 2003).…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies suggested an association between PAI-1 −844 A>G and the 4G/5G polymorphisms and vascular complications in non-insulin-dependent diabetic individuals [35,36]. Moreover, fasting insulin levels, triglycerides and BMI have also been associated with the 4G/5G in subjects with hyperlipidaemia and premature coronary disease or non-insulin-dependent diabetes in Caucasians [24,37,38], but not in all tested populations [39,40].…”
Section: Discussionmentioning
confidence: 99%